Current trends and prospects of the global IT-services market development - Кошкарьова, Єлизавета Леонідівна (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2016)
The modern trends of information services market have been considered as well as an analysis of its current state has been carried out. The main exporters and importers of ICT have been defined. The main directions of development of the global information services market have been determined.